The use of kinesiotaping in the rehabilitation of women after mastectomy with long pectoral nerve damage- case stady - Filarecka, Agnieszka; Kuczma, Monika; Kocik-Bakowska, Natalia; Jabłoński, Wiktor; Malek, Michal; Hozakowski, Mateusz; Gorecki, Wojciech (Journal of Education, Health and Sport, 2019)
Breast cancer is the most common cancer occurring in the female population. Early diagnosis and appropriately implemented treatment results in high curability. The method of choice is surgery, depending on the extent of the changes, a radical method is used, consisting in complete removal of the mammary gland, or sparing. Additional, complementary methods of treatment are radiation, chemotherapy and hormone therapy. Surgery involves interference with tissue continuity and hence scarring. During the procedure, mechanical long pectoral nerve injury may also occur. The paper presents an example of a case study using kinesiotaping as a complementary method of rehabilitation of women after mastectomy with long pectoral nerve damage. The paper analyzes available literature and own experience